The effectiveness of CIRC learning model and PQ4R learning model on reading comprehension skills of elementary school students - Asih Wahyuningsih; Godlove Elioth Kiswaga (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This study aims at identifying the effectiveness of Cooperative Integrated Reading Composition (CIRC) Learning Model on Reading Comprehension Skills, the Preview Question Read Reflect Recite Review (PQ4R) Learning Model on Reading Comprehension Skills and the differences in terms of effectiveness between the two learning models on the Reading Comprehension Skills of Grade V students in elementary school. The study was quasi-experimental research with pretest, posttest non-equivalent group design. The sample for this study was taken from Grade V students from Task Force 1 Lendah Kulon Progo. Simple random sampling technique was applied to select samples. Then, in order to identify the effectiveness of CIRC Learning Model and PQ4R Learning Model collected data were analysed by running the t-test and the ANOVA with the assistance of SPSS software version 22. The results of the study show that both CIRC and PQ4R have been effective for exercising the Reading Comprehension Skills with significance rate 0.000 0.050. However, both models are insignificant for exercising the Reading Comprehension Skills to the Grade V students with significance rate 0.828 0.050.